Usability Analysis of User Interface (UI) Design Using the Heuristics Method on Library Website - Febri Nahla; Salsabila Guspayane; Asyfiya Qurratal Jamilah (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2024)
The library website is an important portal for users to access information, especially in the context of education and research. An evaluation of the quality of the Yogyakarta State University library website was conducted to ensure that the site meets the principles of usability, using the heuristic method developed by Jacob Nielsen. This method aims to determine usability issues in user interface design. Observation of the library.uny.ac.id website shows several problems with the user interface that can affect user experience. This research aims to evaluate and provide recommendations for improvements to the usability of the interface design of the Yogyakarta State University library website. This research method is qualitative through a literature approach that involves a critical and in-depth study of various library materials relevant to the topic of the problem. The results of the study are expected to be information and evaluation materials to develop programs and improve the library website to make it more attractive, informative, innovative, and easy to use by all users. This evaluation also emphasizes the importance of easy access, attractive appearance, and user-friendly design to increase user satisfaction and prevent them from switching to other better websites.